The Effect Of Healthy Lifestyle And Word Of Mouth On Purchase Decision Supplement Product Post Pandemic Covid 19 - Shalahuddin; Lalu Supardin; Diana Leli Indratno; Heru Kuncorowati; Heru Noor Rokhmawati (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
This study aims to examine the effect of healthy lifestyle and word of mouth on purchase decision supplement product post pandemic Covid-19. The number of respondents in this study were 100 respondents. Sampling was done by purposive sampling technique. This study uses multiple linear regression analysis technique with SPSS as an analytical tool. The results of multiple linear regression test indicate that: (1) Healthy lifestyle partially has a significant effect on purchase decision supplement product post pandemic pandemic Covid-19 at Yogyakarta. (2) Word of mouth partially has a significant effect on purchase decision supplement product post pandemic pandemic Covid-19 at Yogyakarta. (3) Healthy lifestyle and word of mouth simultaneously have a significant effect on purchase decision supplement product post pandemic pandemic Covid-19 at Yogyakarta